Psychoeducation in Family with Clients Recovering from the Risk of Violent Behavior (Indian Journal of Public Health Research & Development, 2022)
Recovery is a change in which a person improves his health and well-being, lives in the direction of life he chooses,and strives to achieve life goals according to all his abilities. Recovery conditions are very necessary for everyclient with mental disorders (ODGJ), where strengthening hope, especially from within ODGJ itself, activates themto be active independently with family, friends, and the community in their environment. ODGJ with ViolentBehavior has anger that is expressed excessively and is not controlled verbally to the point of injuring others andor not harming the environment. Through this research with a pre-test-posttest control group design. The resultsfound in this study, it was found that the average recovery rate of ODGJ in the intervention group was 116.17 andthe average recovery rate of ODGJ in the control group was 94.03 so it can be concluded that the average recoveryrate of the intervention group was 22.14 greater than the control group with a significance of P-Value < 0.05. Theresults showed that there was a significant difference in the recovery rate of ODGJ in the intervention group andthe control group. There was also an increase in the recovery rate in the control group, this was possible becauseof other interventions to increase the recovery of ODGJ with the risk of violent behavior either in the form ofindividual, family, or community interventions. Thus, to take sides with all elements in the ODGJ environment,encourage a sustainable family psychoeducation program policy, and be accompanied by monitoring of familycapabilities, especially effective communication within the family in the form of regular family visits by utilizing atiered health facility system.
Keywords: Family, Psychoeducation, The Recovery, Clients with Mental Disorders (ODGJ), The Risk of Violent Behavior